Cell-free protein synthesis and vesicle systems for programmable therapeutic manufacturing and delivery - Wonhee Kim; Jinjoo Han; Shraddha Chauhan; Jeong Wook Lee (Journal of Biological Engineering)
Abstract The convergence of cell-free protein synthesis (CFPS) and vesicle-based delivery platforms presents a promising avenue for therapeutic development. The open environment of CFPS offers precise control over protein synthesis by enabling the modulation of synthetic conditions. Additionally, vesicle-based platforms provide enhanced stability, bioavailability, and targeted delivery. This synergy facilitates the efficient production of complex proteins—including membrane proteins, antibody fragments, and proteins requiring post-translational modifications (PTMs)—and supports novel drug delivery strategies. While existing reviews have covered synthetic cells and biomanufacturing broadly, a dedicated analysis of CFPS system-containing vesicles (CFVs) for therapeutic applications remains absent from the literature. This review addresses this knowledge gap by providing a comprehensive examination of CFVs, highlighting their potential as programmable drug delivery platforms through the integration of genetic circuits. It emphasizes the advantages of CFPS over traditional cell-based approaches and explores the synergistic benefits of combining CFPS with various vesicle systems. These systems offer dynamic control over therapeutic protein production and targeted delivery, enabling precise responses to specific signals in complex environments. Although challenges such as low protein yield and imperfect targeting remain, potential optimization strategies are discussed. This analysis highlights the significant potential of integrating CFPS and vesicle-based delivery to advance biomanufacturing, therapeutic development, and synthetic cell systems, thereby opening new avenues in medicine and healthcare.